Evaluation of Spectrophotometric Methods for Assessing Antioxidant Potential in Plant Food Samples—A Critical Approach - Eliza Knez; Kornelia Kadac-Czapska; Małgorzata Grembecka (Applied Sciences)
Spectrophotometric antioxidant assays can generally be divided into two fundamental categories: single electron transfer (SET)-based assays and hydrogen atom transfer (HAT)-based methods. In SET-based assays, the progression of the electron exchange reaction is determined by the redox potential of the substrates. In contrast, HAT-based methods assess the antioxidant’s ability to transfer a hydrogen atom to a radical, thereby stabilizing it. The objective of this article is to provide a critical evaluation of antioxidant spectrophotometric assays. Assessing the antioxidant potential of food should involve multiple assays to ensure accuracy and reliability. A positive correlation among different methods enhances the validity of the results. Moreover, antioxidants may interact with other food components, such as amino acids, potentially leading to inaccurate outcomes—as observed in the Folin–Ciocalteu assay. Among the various techniques, CUPRAC and ORAC exhibit greater repeatability and reagent stability compared to other assays. Furthermore, these methods are considered superior due to their closer resemblance to in vivo conditions. In contrast, approaches such as ABTS+, DPPH, FRAP, and Folin–Ciocalteu are often criticized for their non-physiological environments. There is a pressing need to establish a standardized method that, to the greatest extent possible, reflects in vivo conditions and can serve as a reference standard for other assays.